Pengembangan Kopi Robusta Temanggung: Temuan dan Bukti dari Jawa Tengah, Indonesia - Danang Purwanto; Widiyanto Widiyanto; Hanifah Ihsaniyati; Raden Roro Ilma Kusuma Wardani; Fajar Julian Santosa (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2023)
Temanggung robusta coffee is a potential plantation commodity in Central Java that has existed since the colonial era. Its development has gone through various policies, both from the top down and bottom up. This research was based on empirical facts and phenomena on the development of Temanggung robusta coffee. The researchers conducted participatory observations, discussions, and in-depth interviews with 15 informants. Data analysis was done through a socio-historical and descriptive approach to accurately understand the evidence, history, and correlations between phenomena. This study’s results prove that the transformation stage of Temanggung robusta coffee began in the era of forced cultivation of “Koffie Stelsel” through patron-client relationships. This development continues to experience socio-cultural shifts with a variety of different policies. Currently, three sectors are the main players in Temanggung robusta coffee (government, large private plantations, and the community). The factors causing the success of Temanggung coffee not to be achieved are 1) the large area of land but low productivity; 2) the process of randomly picking coffee; 3) policies that are not yet optimal; 4) minimal market share; 5) the capacity of extension agents in the coffee commodity is still low; 6) lack of cooperation between stakeholders.